Disaster response and recovery: Aid and social change. Issue 1 (May 2016) - ZHANG, QIAOYUN
Abstract : This article offers a discussion of the complex and far‐reaching impacts that disaster aid has on the socio‐ecological and cultural‐political transformation of affected communities through three different and interrelated theoretical and ethnographic angles presented in the "Response and Recovery" section of the plenary session on the anthropology of risk, hazards, and disasters. It introduces the research on "disaster narratives, " the framing of "bad victims, " and state‐led recovery of ethnic cultures by Mark Schuller, Roberto Barrios, and Qiaoyun Zhang respectively. Responding to the special issue's uniting theme of "continuity and change, " this article analyzes the historical, discursive, political, and social relationships embedded in relief efforts and recovery projects that can induce long‐term change in social lives and relations. It argues that the restoration and endurance of the pre‐disaster ecologically and culturally shaped practices and relationships largely depend on how disaster, damage, and survivors are perceived and manipulated. It observes the oftentimes contested social changes with disaster aid (or lack thereof), reconstruction policies, and recovery projects. Revealing the indigenous adaptation and struggles under imposed reconstruction and resettlement plans, this article hopes to bridge the epistemological and practical gaps between the work of the humanitarian agencies and the needs of the affected populations.